KELAYAKAN USAHA PUDING LAMOTA DITINJAU DARI ASPEK BENEFIT COST RATIO DAN PAYBACK PERIOD - Mia Maelani; Elliza Rizki Wandani; Hasdita Elies Ramadani; Elisa Juniarti; Elsa Rahmawati (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
The Lamota Pudding business is one of the new businesses that students of the Faculty of Economics and Management, Samawa University, Sumbawa Besar, are involved in. As a new business, before the business is developed or before carrying out a business expansion, it is better to carry out a feasibility analysis of the business so that there is an overview of the sustainability of the business in the future. There are several aspects of feasibility from an economic perspective including the Net Benefit Cost Ratio and Payback Period. The results of the analysis show that the B/C ratio of the Lamota Pudding business is 1.15. These results show a B/C ratio > 1, so the Lamota Pudding business is feasible to continue. Meanwhile, the Payback Period (PP) for the Lamota Pudding business was obtained for 1 year, meaning that the Lamota Pudding business was able to return investment costs after the business lasted for 1 year. This is of course relatively fast so that the business is feasible to run.